Vida e teatro em Guimarães Rosa: Grande sertão: veredas e pirlimpsiquice - Bolognesi, Mario Fernando [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 1985)
Este artigo inicia-se com uma exposição sucinta da metáfora do teatro, tal como aparece em Platão. em seguida, após levantamento dos momentos capitais da literatura, investiga-se a metáfora em Guimarães Rosa, no Grande sertão: veredas e no conto Pirlimpsiquice. No Grande sertão, a atuação no palco é tomada como equivalente ao desempenho na vida. Teatro e vida são, portanto, domínios que se identificam. Para isto, concorrem a religião cristã e o pensamento de Plotino. em Pirlimpsiquice, o Autor investiga por menorizadamente os limites e aproximações entre teatro e vida, sendo que o grau mínimo da metáfora é conferido pelas práticas histórica e cultural. Por fim, retomando a polêmica de Hegel com o platonismo, conclui-se que a representação e a vida estão amalgamadas, numa constante dialetização entre história e cultura.

This article is introduced with a summarized discussion on the theater's metaphor as considered by Plato. It goes on considering several turning points in the literature history and investigating the different uses of the metaphoric process in Guimarães Rosa Grande sertão: veredas and Pirlimpsiquice. Firt of all, in Grande sertão life is considered as a simbolic equivalent to actors performance in the stage: theater and life are seen, therefore, as concerning fields which identities can be stated upon christian religious doctrine and Plotino's philosophy. on the other hand, in Pirlimpsiquice, Guimarães Rosa points that the limits between life and theater fields can be sharply identified, leading to the conclusion that the different degrees of use of the metaphoric process is due to historical and cultural practices. Based on the theoric controversy between Hegel's and Plato's points of view on art's philosophy, the author concludes that the notions of performance in the stage and performance in life are sintetized under the continuous dialectic movement of history and culture.
Theater and life aspects in Guimarães Rosa literature: Grande sertão: veredas and Pirlimpsiquice
Keywords: Literatura; teatro; teoria de teatro; literatura brasileira; Literature; theater; theory of theater; Brazilian literature